Data-Snooping Biases in Tests of Financial Asset Pricing Models - Lo, Andrew W.; MacKinlay, A. Craig (Review of Financial Studies, 1990)
Tests of financial asset pricing models may yield misleading inferences when properties of the data are used to construct the test statistics. In particular, such tests are often based on returns to portfolios of common stock, where portfolios are constructed by sorting on some empirically motivated characteristic of the securities such as market value of equity. Analytical calculations, Monte Carlo simulations, and two empirical examples show that the effects of this type of data snooping can be substantial.